Role of chemokine receptors in thyroid cancer and immunotherapy. Issue 8 (August 2019) - Coperchini, Francesca; Croce, Laura; Marinò, Michele; Chiovato, Luca; Rotondi, Mario
Abstract : Inflammation is currently regarded as an essential component of malignancies. It is now known that the tumor microenvironment may profoundly influence the biological behavior of cancer cells and ultimately the patient's outcome. Chemokine and their receptor play a major role in determining the immune phenotype of the cells infiltrating the thyroid tumor microenvironment. Experimental evidence shows that both normal and cancer thyroid cells express specific chemokine receptors. The expression of at least some of these receptors exerts several biological effects, which influence the course of the disease. The present review article will take into account the role of the most studied chemokine receptors (CXCR1, CXCR2, CXCR3, CXCR4, CXCR7, DARC, CCR3, CCR6 and CCR7) in the context of thyroid cancer. This review will focus on current knowledge provided by in vitro and in vivo studies specifically performed on thyroid cancer including (i) expression of chemokine receptors in normal and cancer thyroid cells; (ii) role of chemokine receptors in affecting the biological behavior of thyroid tumors including the metastatic process; (iii) current knowledge about immunotherapies through targeting of chemokine receptors in thyroid cancer.